Verification and analysis of the sustainable and responsible posture of leaders and the presence of TBL in an agroindustry: content analysis based on Iramuteq and main interview points - Gaião, Luis Fernando Brandão; Hayashi Junior, Paulo (Revista de Administração da UFSM, 2025)
Purpose: This article seeks to analyze and describe the occurrence of the main aspects of the eight categories that make up the Sustainable and Responsible Leadership Framework, explained in the article, in the performance of leaders in a Brazilian agroindustry company. Design/Method/Approach: This is a qualitative, inductive, and descriptive study carried out by a case study in a company. Semi-structured interview script and non-participant observations were used. Content analysis was conducted by reading and consolidating interviews, as well as by descending hierarchical classification (DHC) of words using Iramuteq software. Findings: The main aspects identified in the interviews that make up the constructs sustainable and responsible posture of leaders are presented, highlighting the ethical posture when promising and fulfilling; care for goals and results, suppliers and customers, and the community; and respect for diversity. The presence of contemporary aspects of the Triple Bottom Line (TBL) was also examined in the leaders’ performance, but with greater emphasis on the Economic Pillar (Production). Practical implications: The study reinforces the importance of companies being aware of the sustainable and responsible posture of leaders in Brazilian agribusiness, a sector in constant transformation. Originality/Value: As a contribution, we propose a Sustainable and Responsible Leadership Framework and we indicate the main aspects of the performance of leaders as drivers for obtaining broad results in the TBL in agribusiness.